METHOD FOR DETERMINING THE CONDUCTIVITY DISTRIBUTION OF DOPED SAMPLES - Samatov, A.M; Jalalov, R.M; Fayzullaev, K.M (Educational Research in Universal Sciences, 2023)
This work describes a four-probe method for measuring the resistivity of semiconductor materials doped with different dopant atoms. The article presents the requirements for the size and shape of the samples that are the object of research.